Design of a Corner-Reflector Reactively Controlled Antenna for Maximum Directivity and Multiple Beam Forming at 2.4 GHz - Dimousios, T D; Mitilineos, S A; Panagiotou, S C; Capsalis, C N (IEEE transactions on antennas and propagation, 2011)
Electronically steerable passive array radiator (ESPAR) antennas constitute a promising research field and are expected to play important role in future wireless communications. In this paper, a new approach in ESPAR antenna design for base station applications is proposed. A corner-plate reflector is combined with active and passive (reactively loaded) elements in order to implement a corner-reflector ESPAR (CR-ESPAR) configuration. It is shown that when combined with corner reflectors in order to sectorize the coverage area, an ESPAR antenna offers multiple radiation patterns with higher directivity and resolution. A case study of a CR-ESPAR suitable for 2.4 GHz ISM applications is demonstrated, where the performance of the structure is optimized with respect to resonance frequency, input impedance, and multiple switched-beam patterns configuration. The optimization of the array is performed using a Genetic Algorithm (GA) tool as a method of choice, achieving a maximum gain equal to 14 dBi for a 30°3 dB-beamwidth and a gain of 11 dBi for a 45°3 dB-beamwidth, while the VSWR is kept below 1.7 in all cases. Due to its limited physical size, the proposed CR-ESPAR can be used as a portable antenna for deployment in WiFi, WLAN and other applications.